THE USE OF ANTHROPONYMS IN THE WORKS OF POET - Koylibayeva, Hurliman; Abdinazimov, Sh (Innovative Development in Educational Activities, 2023)
Karakalpak human names are part of the vocabulary of the language. It takes its channel from the fond of the common folk language and is developed according to the internal rules of our language. Thus, it is made from all the branches of words in the language. The majority of Karakalpak human names clearly show the cultural and historical life of our people from ancient times to the present. In our article, we focused on the usage differences of anthroponyms in the works of I. Yusupov, anthroponyms of historical figures or contemporaries, anthroponyms of images in other literary works, anthroponyms of mythological and folkloric images, anthroponyms of derivative images.